Mission hurricane [compact disc, unabridged] - Goebel, Jenny (39 clues. Doublecross., 2016)
Who is the Outcast and why is he threatening the lives of innocent people? Book three reveals a shocking secret that will send Amy and Dan, and the world, reeling.